Development and evaluation of protective immunity of a ROP27 DNA vaccine against Eimeria tenella in chickens - Wenrui Zhao; Zhibin Niu; Kuihao Liu; Xueqi Zhang; Shuning Kang; Kewei Dou; Jiaqi Zhao; Rui Bai; Mingxue Zheng; Xiaoling Lv (Poultry Science)
This study aimed to develop and evaluate the protective immunity of a ROP27 DNA vaccine against Eimeria tenella (E. tenella) in chickens. E. tenella is a parasitic protozoan that poses a significant threat to the poultry industry. The rhoptry protein 27 (ROP27) of E. tenella has been shown to have immunoprotective properties. However, traditional protein expression methods are time-consuming and labor-intensive, limiting large-scale production. In this study, we developed a pVAX-ROP27 DNA vaccine and confirmed its expression in chickens using RT-PCR and Western blot analysis. The protective immunity of the DNA vaccine was evaluated through an animal experiment with different immunization doses. The results confirmed the successful construction of the pVAX-ROP27 DNA vaccine and its in vivo expression. Chickens immunized with the vaccine at different doses showed significant improvements in average weight gain, relative weight gain rate (RWG), cecal lesion score reduction (RLS), and oocyst reduction rate, as well as a decrease in oocysts per gram (OPG). The group immunized with 100 μg/feather of pVAX-ROP27 exhibited the most significant effect, achieving an anticoccidial index (ACI) of 179.80. Additionally, levels of IL-2, IFN-γ, IL-6, IgG, and IgY significantly increased with the number of immunizations, whereas IL-4 and IL-10 showed no significant differences. Histopathological analysis of the ceca revealed that lesions were least severe in the 100 μg/feather pVAX-ROP27 immunized group. These findings suggest that the pVAX-ROP27 DNA vaccine offers immune protection against E. tenella infection and could serve as a promising candidate for preventing and controlling chicken coccidiosis.